Clinical and pathological features of donor/recipient body weight mismatch after kidney transplantation. (July 2015) - Yamakawa, Takafumi; Kobayashi, Akimitsu; Yamamoto, Izumi; Nakada, Yasuyuki; Mafune, Aki; Katsumata, Haruki; Furuya, Maiko; Koike, Kentaro; Miki, Jun; Yamada, Hiroki; Tanno, Yudo; Ohkido, Ichiro; et al.
Abstract: Background: Previous studies have shown that a donor/recipient body weight mismatch affects long‐term graft survival and graft function after kidney transplantation. However, the mechanisms are not fully understood. Aim: To address the mechanisms, we compared the pathological and physiological features between patients with a donor/recipient body weight mismatch and those without a mismatch 1 yr after kidney transplantation. Furthermore, we investigated the correlation with the donor/recipient body weight ratio. Methods: We examined allograft biopsy specimens from 10 recipients with stable kidney function, with body weight mismatch (donor/recipient body weight ratio [D/R BWR] < 0.9), and compared them with samples from 13 patients without mismatch. We measured glomerular volume (GV) using the Weibel–Gomez method and glomerular density (GD) defined by nonsclerotic glomerular number/renal cortical area as pathological findings. The physiological parameters included estimated glomerular filtration rate and proteinuria (mg/day). These data were evaluated to identify a correlation with D/R BWR. Results: The pathological features showed that GV and GD were identical in the two groups. However, when glomerular enlargement was defined by ΔGV (GV at the 1‐yr biopsy minus GV at baseline biopsy), ΔGV was higher in mismatch cases compared with that in cases without a mismatch (10.6 ± 4.6 vs. 5.5 ± 7.1 × 10 5 μm 3 ; P = 0.049). Furthermore, D/R BWR was significantly correlated with ΔGV ( P = 0.03, r = –0.436). eGFR values were physiologically identical between the two groups, but the mismatch cases had significantly higher proteinuria levels than that of the cases without a mismatch at 1 yr after kidney transplantation. Conclusion: A donor/recipient body weight mismatch could affect glomerular enlargement and increased proteinuria 1 yr after kidney transplantation. How these two features affect long‐term graft survival and function must be addressed in the future.